1972
DOI: 10.1172/jci106983
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Interaction between Collagen and a Plasma Kallikrein-Like Activity EVIDENCE FOR A SURFACE-ACTIVE ENZYME SYSTEM

Abstract: A B S T R A C T This study has demonstrated that collagen particles, after exposure to platelet-poor human plasma and subsequent washing, generate a kinin-like agent when incubated with prekinin substrate. The binding of kinin-generating activity to collagen in the plasma collagen incubation mixture occurs rapidly, whereas the loss of this activity in the incubation mixture occurs relatively slowly. The Hageman factor appeared to be necessary for the surface-bound kiningenerating activity, as this activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…This is consistent with the recent demonstration of the binding of plasma kallikrein to collagen and the kinin-releasing capability of the surface-bound kallikrein (20).…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the recent demonstration of the binding of plasma kallikrein to collagen and the kinin-releasing capability of the surface-bound kallikrein (20).…”
Section: Resultssupporting
confidence: 92%
“…To provide even stronger evidence that all detectable fibrinogenolytic activity was closely associated with a2-macroglobulin, the relationship of a2-macroglobulin to its proteolytic activity was further explored by immunoprecipitation. An IgG fraction, itself possessing no antiplasmin activity as demonstrated by a fibrinolytic assay (39), having antibody specific for a2-macroglobulin, was added in optimal amounts (40) to the a2-macroglobulin prepared from urokinasetreated plasma. After removal of the precipitate which formed after an 18-h incubation at 40C, the supernatant fluid contained no detectable a2-macroglobulin as determined by electroimmunoanalysis (28).…”
Section: Resultsmentioning
confidence: 99%
“…The values given are derived from integration of reduced radiolabeled prekallikrein in the 85,000 Mr uncleaved molecule and the 48,000 Mr cleavage fragment shown in Fig. 2 Harpel (34) showed that partially purified kallikrein would bind to collagen and that, after brief incubation of particulate collagen with undiluted plasma, kallikrein activity could -be identified on the washed collagen. Assuming …”
Section: Factor XImentioning
confidence: 99%